Multicomponent redox gradients on photoactive electrode surfaces - Guldi, Dirk Michael; Zilbermann, Israel; Anderson, Greg; Lin, Andrew; Balbinot, Domenico; Jux, Norbert; Hatzimarinaki, Maria; Hirsch, Andreas; Prato, Maurizio (Chemical Communications, 2004)
Redox gradients have been used to tailor the arrangement of photoactive ITO-electrodes at the molecular level.